PERANCANGAN MEDIA INFORMASI UNTUK MENANGGULANGI KECANDUAN GAWAI PADA ANAK - Evelyn Lumanta; Peter Rhian Gunawan; Miki Tjandra (Serat Rupa: Journal of Design, 2019)
Research has shown that gadgets can give negative impacts on children, especially those on the early childhood stages. The development side of the early childhood stages is pertained to be vital and important for their growth, and it can be damaged permanently by the overuse of gadgets. One of the important factor is parent’s lack of knowledge about this damage on the early childhood stage, hence there is a need for an informative media about the damage on gadgets addiction on early age children. The purpose of this project is to provide an informative media that can clarify the damage of this gadget addiction, and also to give the parent’s the solution for the addictions. With the appropriate applications of UI (User Interface) and UX (User Experience) design, the right informative media can give clear information for the parents to be wise on their kid’s gadgets usage. The methods used in this design are based on qualitative research dan development method, implementing research from literature studies, interview, survey and field observation. The collected datas are explained and made into conclusion. The conclusion is used as the base of the informative media design. The final results will take form in website, as it is accessible from many locations, and ambient media as one of the ways to bring back the awareness for this issue. The informative medias would be made as attractive as possible so it is interesting and easier to understand for the parents of the early age children.